Can we trust this short scale? Validation of a Brief Self-Report Measure of Epistemic Trust, Mistrust and Credulity (ETMCQ-R-6) in a sample of the U.K. general population - David Riedl; Henry Delamain; Peter Fonagy; Astrid Lampe; Samuel Eke; Tobias Nolte; Hanna Kampling; Johannes Kruse; Chloe Campbell (PLOS Mental Health, 2026)
The concept of the epistemic stance (i.e., an individual’s openness to learning from others) has been increasingly recognized as a key construct associated with mental health. This study validated a six-item short form of the Epistemic Trust, Mistrust and Credulity Questionnaire (ETMCQ-R) in a UK quota-balanced community sample (N = 515). Using stepwise item reduction and confirmatory factor analysis, a three-factor structure with two items per subscale (trust, mistrust, credulity) was identified. The ETMCQ-R-6 showed acceptable fit (scaled χ² (6)=22.13, p = .001; robust CFI = .978; robust TLI = .945; robust RMSEA = .073 [90% CI: .042, .107]; SRMR = .029) and acceptable reliability for the trust (α = .75) and credulity (α = .77) subscales, while the mistrust subscale fell below the conventional threshold (α = ρ = ω = .68). Configural, metric, scalar, and structural invariance across gender and age groups was supported, while strict invariance was not established. Correlations between the long and short form were high (r = 0.83–0.87; φ = 0.95–1.00). Hierarchical regression analyses confirmed significant incremental predictive validity for epistemic mistrust and credulity across psychopathology outcomes, while the trust subscale demonstrated domain-specific incremental validity for attachment avoidance. The ETMCQ-R-6 offers a brief, psychometrically stable assessment of epistemic stance suitable for epidemiological research.